Modelling of Hybrid Materials and Interface Defects through Homogenization Approach for the Prediction of Effective Thermal Conductivity of FRP Composites Using Finite Element Method - C. Mahesh; K. Govindarajulu; V. Balakrishna Murthy (Advances in Materials Science and Engineering)
Finite element method is effectively used to homogenize the thermal conductivity of FRP composites consisting of hybrid materials and fibre-matrix debonds at some of the fibres. The homogenized result at microlevel is used to determine the property of the layer using macromechanics principles; thereby, it is possible to minimize the computational efforts required to solve the problem as in state through only micromechanics approach. The working of the proposed procedure is verified for three different problems: (i) hybrid composite having two different fibres in alternate layers, (ii) fibre-matrix interface debond in alternate layers, and (iii) fibre-matrix interface debond at one fibre in a group of four fibres in one unit cell. It is observed that the results are in good agreement with those obtained through pure micro-mechanics approach.